A practical community-based response strategy to interrupt Ebola transmission in sierra Leone, 2014–2015. Issue 1 (December 2016) - Li, Zhong-Jie; Tu, Wen-Xiao; Wang, Xiao-Chun; Shi, Guo-Qing; Yin, Zun-Dong; Su, Hai-Jun; Shen, Tao; Zhang, Da-Peng; Li, Jian-Dong; Lv, Shan; Cao, Chun-Li; Xie, Rui-Qian; et al.
Abstract Background The Ebola virus disease spread rapidly in West Africa in 2014, leading to the loss of thousands of lives. Community engagement was one of the key strategies to interrupt Ebola transmission, and practical community level measures needed to be explored in the field and tailored to the specific context of communities. Methods First, community-level education on Ebola virus disease (EVD) prevention was launched for the community's social mobilizers in six districts in Sierra Leone beginning in November 2014. Then, from January to May of 2015, in three pilot communities, local trained community members were organized to engage in implementation of EVD prevention and transmission interruption measures, by involving them in alert case report, contact tracing, and social mobilization. The epidemiological indicators of transmission interruption in three study communities were evaluated. Results A total of 6 016 community social mobilizers from 185 wards were trained by holding 279 workshops in the six districts, and EVD message reached an estimated 631 680 residents. In three pilot communities, 72 EVD alert cases were reported, with 70.8 % of them detected by trained local community members, and 14 EVD cases were finally identified. Contact tracing detected 64.3 % of EVD cases. The median duration of community infectivity for the cases was 1 day. The secondary attack rate was 4.2 %, and no third generation of infection was triggered. No health worker was infected, and no unsafe burial and noncompliance to EVD control measures were recorded. The community-based measures were modeled to reduce 77 EVD cases, and the EVD-free goal was achieved four months earlier in study communities than whole country of Sierra Leone. Conclusions The community-based strategy of social mobilization and community engagement was effective in case detection and reducing the extent of Ebola transmission in a country with weak health system. The successfully practical experience to reduce the risk of Ebola transmission in the community with poor resources would potentially be helpful for the global community to fight against the EVD and the other diseases in the future.